Experimental demonstration of a unified framework for mixed-state geometric phases - Zhu, J; Shi, M; Vedral, V; Peng, X; Suter, D; Du, J (2011)
Geometric phases have been found in every major branch of physics and play an important role in mathematics and quantum computation. Here, we unify two proposed definitions of the geometric phase in mixed states - Uhlmann's phase and Sjöqvist's phase - in a new formalism based on interferometry and further provide an experimental demonstration in NMR. This is also the first experimental measurement of Uhlmann's geometric phase. © 2011 Europhysics Letters Association.